Networking is a contact sport : How Staying Connected and Serving Others Will Help You Grow Your Business, Expand Your Influence -- or Even Land Your Next Job - Sweeney, Joe, ....-; Yorkey, Mike, ....- (Dalles : Benbella Books, 2010)
How did Joe Sweeney... ...get Bob Costas to come to Milwaukee (in the middle of winter)?...become the wingman to the archbishop of New York City?...take Brett Favre's off-the-field income from $65,000 to more than $4 million? The answer is simple. Networking. In this New York Times, Wall Street Journal, and USA TODAY bestseller, master networker Joe Sweeney shares his networking secrets from a long and successful career as a business owner, sports agent and executive and investment banking consultant. His first secret: master networkers are focused on giving, not getting. With today's difficult economy and uncertain workplace, networking has never been more important. Sweeney's simple but effective 5/10/15 networking plan will give you a leg up in the current job market, help you stay employed, or, if you've been laid off, find your next job. The cliche that who you know is more important than what you know has never been truer. Sweeney illustrates his insights with dozens of helpful examples from his own life (along with a few fascinating insider sports stories). With special sections on networking for women and minorities, insights into the usefulness (and handicaps) of social networking sites, how to get (and why you need) a wingman and profiles of other master networkers, Networking Is a Contact Sport is a practical and essential guide for anyone who wants to get ahead in today's economy.